The meaning of metamodern spirituality: beyond modern and postmodern perspectives on the religious and the secular - Vliegenthart, Dave (Journal of contemporary religion, 2025)
Is contemporary spirituality a modern, postmodern or metamodern category? This article claims that contemporary spirituality is a metamodern category because it clearly shows both modern and postmodern tendencies. This claim is supported by a case study of ‘grassroots spirituality’. Grassroots spirituality shows modern tendencies in its Enlightenment pursuit of rationality, liberty, equality, and democracy as well as in its Romantic search for transcendence within immanence, with a focus on experience. Grassroots spirituality shows postmodern tendencies in its commodification of fragments from different traditions, according to the cultural logic of late capitalism, as well as in its distrust and deconstruction of grand narratives, resulting from a relativization of language and belief systems. Its oscillations between modern and postmodern tendencies make contemporary (grassroots) spirituality metamodern.